PERTANGGUNGJAWABAN BANK DALAM MEMBERIKAN GANTI RUGI TERHADAP NASABAH ATAS RISIKO OPERASIONAL (CONTOH KASUS PADA PT BANK MANDIRI) - Sofwatun Nida; Jeane Neltje Saly (Fakultas Hukum Universitas Tarumanagara, 2020)
In the current era of globalization, banks are one of the financial institutions entrusted by customers in saving their assets. In carrying out its activities, banks must comply with the rules and principles stipulated in Act Number 10 of 1998 concerning Amendments to Act Number 7 of 1992 concerning Banking. There are many phenomena that occur between banks and customers, one of which is the application of weak prudential principles, such as disruption of the bank system that causes changes in customer balances, there are some customers whose balances have increased and there are also customers whose balances have decreased, causing losses to customers. From this issue, what will be discussed is how the accountability of the bank to the injured customer with the aim of knowing what the customer should do if he feels aggrieved by the bank, and to know what can and should not be done by both parties. If the bank is proven to have committed an activity that caused losses to the customer, the bank is obliged to be responsible for and for damages.